Efisiensi Biaya Distribusi Produk Stone Crusher Plant - Pratama, Rizqi Fajar; Wicaksono, Leo Hutri; Hermawan, Dadang (Widyagama University of Malang, 2024)
In the utilization of natural products, one of which is stone, has a variety of functions and many industrial sectors require these products with certain sizes and specifications. The high demand must of course be in line with the availability of products of course with a variety of market demand criteria. From the industrial sector, careful planning needs to be done such as the risk when running production. Determining the right tool is needed to be optimal. As well as being able to maintain commitment to customers. The productivity of Stone Crusher plays a full role as the selling point of the stone products produced. Of course, understanding the production capacity of the tool is very necessary to maintain commitment with consumers and minimize the non-achievement of consumer demand. In the stone crusher project in Medan based on the analysis of production of 100 tons / hour or 71.42 m3 / hour for 8 hours of production with a stone density of 1400 kg / m3, the transport capacity is 200 m3 / day.